Psychological Empowerment of Secondary School Principals in Sarawak - Britten, Linton @ Jerah (2003)
This study is an attempt to assess the level of, and the factors associated with, psychological empowerment of secondary school principals in Sarawak. Two groups of respondents were involved in the study: the school principals, and classroom teachers of the selected school principals' schools. The target population comprised 131 secondary school principals. Self-administered questionnaires were sent to 117 randomly selected school principals, of which 101 were subsequently used in data analyses. From the 585 sets of self-administered questionnaires sent to the teachers, 458 were useable for data analyses. Five different attitudinal rating scales (or instruments), grouped in two different sets, were used in the study. All the rating scales had reliability estimates (Cronbach's Coefficient Alpha) of above .70. Overall, the degree of felt psychological empowerment as reported by the school principals was mostly at moderate or higher level. There were however, variations across the four PE dimensions. In a nutshell, the levels of empowerment experienced by the sample during the study were found to be generally moderate or higher. Only variables that were more directly related in a personal nature to the school principals indicated some significant relationship with scores on the psychological empowerment concept, either at the composite or dimension levels. As expected, scores on the work motivation, and the withdrawal intentions, showed significant relationship with total scores on PE.